Pengaruh Variasi Core Serat Daun Nanas Dan Temperatur PostCuring Pada Komposit Terhadap Kekuatan Bending Dan Struktur Mikro - Ari Priantama Ari Priantama; Wawan Trisnadi Putra; Nanang Suffiadi Akhmad (Jurnal Teknik Juara Aktif Global Optimis, 2023)
Rapid industrial progress and supported by various innovations that are increasingly using lightweight and strong materials, so that sandwich composite research is needed by utilizing existing natural fibers. Composite is an alloy of various materials which is then made using the Hand Lay Up method to create a material that has characteristics that are ductile, light and strong depending on the elements of the carrying material. The sandwich composite with pineapple leaf fiber core and 40% : 60% fiberglass skin which was processed at 70℃ for 8 hours yielded an average maximum stress of 547,721 Kgf. While the pineapple leaf fiber core and fiberglass skin 50% : 50% at a temperature of 80℃ get an average maximum stress of 437,156 Kgf and at a composition of 60% : 40% temperature 90℃ an average maximum stress is obtained of 225,882 Kgf. Furthermore, at the lowest stress the results of the bending test at a temperature of 70℃ the average bending test value is 312,156 Kgf, in the micro tests carried out it can be seen that there are still quite a lot of cavities at high temperatures causing the bending value to decrease, the higher the temperature and the blend of fibers Pineapple leaf that is applied the lower the bending strength value is done, so it can be concluded that the pineapple leaf fiber does not give the maximum effect to the composite material.Keywords: Sandwich Composite, Post-curing, Pineapple Leaf Fiber, Resin, Bending Test, Micro Structure Test.